(untitled) (Clinics, 2007)
PURPOSE: Data are conflicting concerning the risk for ischemic stroke associated with a common polymorphism in the gene encoding 5,10-methylenetetrahydrofolate reductase C677T, which predisposes carriers to hyperhomocysteinemia. A meta-analysis study suggested that the 5,10-methylenetetrahydrofolate reductase 677TT genotype might have a small influence in determining susceptibility to ischemic stroke. METHODS: We analyzed the 5,10-methylenetetrahydrofolate reductase 677TT genotype polymorphism in Brazilian subjects with ischemic stroke, using a case-control design. RESULTS: We compared 5,10-methylenetetrahydrofolate reductase genotypes in groups of subjects presenting ischemic stroke (n = 127) and normal control (n = 126) and found an odds ratio of 1.97 (95% CI, 0.84-4.64) in a multivariate analysis in which results were adjusted to baseline clinical characteristics of study participants. CONCLUSION: We found that the homozygous 5,10-methylenetetrahydrofolate reductase C677T genotype was not a risk factor for ischemic stroke in these Brazilian subjects.